Investigation of fuel properties and engine analysis of Jatropha biodiesel of Kenyan origin - Maina, Paul (Journal of Energy in Southern Africa, 2014)
Biodiesel was produced from jatropha curcas oil of Kenyan origin through a two-step acid-base catalytic transesterification process. The relevant physicochemical properties of the produced biodiesel were tested according to appropriate standards and were found to be within the requirements. Engine tests were carried out in an Audi, 1.9 litre, turbocharged direct injection, compression ignition engine at different loads. Emissions were measured by a Horiba emission analyser system while combustion data was collected by a data acquisition system, from which, cylinder pressure and rate of heat release of the test engine in every crank angle were calculated. Though the biodiesel had slightly higher brake specific fuel consumption when compared to fossil diesel, its emission behaviour was significantly better. The combustion characteristics were also slightly higher as compared to fossil diesel. This study therefore concluded that biodiesel derived from jatropha curcas of Kenyan origin can be utilized as a safe substitute for mineral diesel.